Ready Medic One: A Feasibility Study of a Semi-Autonomous Virtual Reality Trauma Simulator - Lombardo, Robyn; Walther, Nicholas; Young, Scott; Gorbatkin, Chad; Sletten, Zachary; Kang, Christopher; Tran, Oanh; Couperus, Kyle (Frontiers in Virtual Reality, 2022)
Introduction Virtual reality (VR) technologies have rapidly advanced and offer increasingly higher fidelity visually immersive learning environments. Several studies have shown promise for using VR in medical education. This pilot study evaluates the feasibility of using a novel VR trauma simulator that can function without an instructor, assessing potential challenges with the technology, perceived realism of the simulation, side effects experienced while completing the simulations, and overall perception of training utility from end-users. Methods This was a single-center prospective cohort study completed at Madigan Army Medical Center Emergency Department. Participants were enrolled using convenience sampling. They completed surveys before and after completing a trauma simulation. Each participant underwent a 10-minute simulation orientation and subsequently completed a self-directed trauma simulation involving massive hemorrhage, tension pneumothorax, or airway obstruction case. The simulation utilized a gaming laptop and a Microsoft Mixed Reality© headset and controllers. Survey data was analyzed using descriptive statistics and subgroup analyses. Results Seventeen participants were enrolled and completed pre-and post-surveys. Study participants were predominantly male and represented all clinical roles in the emergency department (ED). Overall, participants indicated the training environment felt realistic (AV 8.3/10, SD 1.4, 95% CI 7.6, 8.0) and supported further use of this technology in training (AV 9.3/10, SD 0.99, 95% CI 8.8, 9.8). There was a statistically significant correlation between participants who responded, “I would support further use of this technology in my training” (Likert greater than 8/10) and several other responses. Individuals who supported further use of VR in training were more likely to have fewer years of clinical experience, have more experience with 2D computer training, reported real clinical changes and environment, and supported the addition of VR to mannequin-based training. Conclusion The results indicate it may be possible to create realistic dynamic VR simulations that function without an instructor and that medical personnel may support integrating VR technology into medical education. This seems most likely for younger individuals with less experience, who have found computer-based medical training helpful in the past. Future research could focus on minimizing side effects and how VR technology can best augment current training techniques and curricula.